Santripreneur: Digital Transformation in Halal Start-Up Management for Islamic Boarding School Students [Santripreneur: Transformasi Digital Dalam Manajemen Start-Up Halal Bagi Santri] - 'Ilmi, Zujajatul; Novitasari, Dwi; Muttaqi'in, Ninnasi; Meutia, Nur Shabrina; Putra, Riyan Sisiawan (Indonesia Berdaya, 2025)
Abstract. Insan Cendekia Mandiri Boarding School (ICMBS) Sidoarjo is a boarding educational institution that provides free education for outstanding orphaned children at the junior and senior high school levels from various regions in Indonesia. This community service activity was carried out under the theme "Santripreneur: Digital Transformation in Halal Start-Up Management for Islamic Boarding School Students." The chosen theme aligns with the activity's objective, which is to enhance digital literacy and sharia-based entrepreneurial insight among the students. Initial observations, conducted through a pre-test, revealed that students’ understanding of business digitalization and knowledge of halal start-ups was still limited. The activity method consisted of three stages: (1) delivering material on digital entrepreneurship, sharia business, and simple business strategies; (2) practicing the production of herbal drinks made from toga plants (ginger, lemongrass, lemon, and pandan), including taste testing; and (3) implementing sustainability through the cultivation of herbal plants as a source of independent raw materials. The results of the activity showed an increase in students' understanding of business digitalization, halal start-ups, and skills in designing simple business models using the Business Model Canvas (BMC). Furthermore, in the future, students will be able to produce herbal products and develop the cultivation of toga plants as a sustainability effort. This activity proves that integrating business digitalization, Islamic values, and local potential can create an adaptive, sustainable, and sharia-based entrepreneurial ecosystem in Islamic boarding schools or boarding schools. Abstrak. Insan Cendekia Mandiri Boarding School (ICMBS) Sidoarjo merupakan sebuah Lembaga Pendidikan asrama yang menyediakan Pendidikan gratis bagi anak-anak yatim berprestasi Tingkat SMP dan SMA dari berbagai daerah di Indonesia. Kegiatan Pengabdian Masyarakat ini dilakukan dengan mengusung tema “Santripreneur: Transformasi Digital dalam Manajemen Start-Up Halal bagi Santri.” Tema yang diangkat disesuaikan dengan tujuan kegiatan, yaitu meningkatkan literasi digital dan wawasan kewirausahaan berbasis syariah bagi para siswa. Observasi awal, melalui pre-test didapati bahwa pemahaman siswa terhadap digitalisasi bisnis dan wawasan tentang start-up halal masih terbatas. Metode kegiatan dilakukan melalui tiga tahap, yaitu (1) pemberian materi kewirausahaan digital, bisnis syariah, dan strategi bisnis sederhana; (2) Praktik produksi minuman herbal berbahan toga (jahe, sereh, lemon dan pandan) termasuk uji rasa; dan (3) Implementasi keberlanjutan dengan budidaya tanaman herbal sebagai penyedia bahan baku mandiri. Hasil kegiatan menunjukkan adanya peningkatan pemahaman siswa mengenai digitalisasi bisni, start-up halal serta keterampilan merancang model bisnis sederhana menggunakan Business Model Canvas (BMC). Selain itu, kedepannya para siswa akan mampu menghasilkan produk herbal dan pengembangan budidaya tanaman toga sebagai upaya keberlanjutan. Kegiatan ini membuktikan bahwa integrasi digitalisasi bisnis, nilai Islami, dan potensi local mampu menciptakan ekosistem kewirausahaan pesantren ataupun sekolah boarding yang adaptif, berkelanjutan dan berlandaskan syariah.